Class Conflict and the Nigerian Labour Movement; Strike, Protests, and Policy Changes - Abunike, Uchenna Evelyn (WritingThreeSixty, 2025)
This article examines the relationship between class conflict and the Nigerian labour movement, focusing on the role of strikes, protests, and the subsequent policy changes. The primary objective is to explore how economic inequalities and class divisions fuel labour activism in Nigeria, particularly through the actions of the Nigerian Labour Congress (NLC) and various trade unions. The study is grounded in conflict theory, which posits that class struggles and economic disparities are key drivers of social and political change. A qualitative approach is employed, utilizing historical records, government reports, and scholarly literature to analyse the evolution of labour movements and their impact on policy development. The findings indicate that labour strikes and protests are pivotal in challenging class disparities and advocating for improved working conditions, fair wages, and social justice. These movements lead to significant policy changes, including reforms in labour laws and wage policies, though the responses from the government and employers are often reactive rather than proactive. The discussion emphasizes the enduring nature of class conflict in shaping labour relations and policy in Nigeria, concluding that continued advocacy is essential to address ongoing inequalities and ensure lasting socio-economic progress. The article underscores the importance of understanding of class conflict as a driving force behind labour activism and its influence on policy reforms in Nigeria.